Manajemen Stres Siswa Madrasah Aliyah Muhammadiyah I Malang - Anggraini, Purwati; Musaffak, Musaffak; Hudaniah, Hudaniah (Yayasan Rahmat Islamiyah, 2024)
Generation Z is said to often experience stress due to socio-economic changes in society. This has an impact on concentration, motivation and smooth learning in class. Several problems arise in learning, one of which is students' learning motivation which tends to decrease. This is caused by several things, including support from parents and the closest environment and unstable emotions. This is what ultimately triggers stress in students. Based on interviews with the deputy principal, teachers have helped students in motivating, encouraging the development of students' talents and interests, as well as communicating with parents and students to find out students' learning progress. The solution offered is stress management assistance for students. Students are invited to explore problems, provide material on psychological health, stress management, games, stress management practices, and finally a stress management evaluation. All mentoring activities are carried out offline and online. Based on physical activities, emotional processing, optimizing talents, interests, religious activities, and thought processing, students become more motivated and gain new experiences in managing stress.Â